Sacred Landscapes Under Siege: "Resolving disputes over mining claims on sacred landscapes in Musina through the legal lens of a Land Court" - Mamabolo, Mokgadi (University of the Witwatersrand, Johannesburg, 2024)
The proposed site for this dissertation is situated in Musina in the Vhembe District, close to the Limpopo River, which forms the border between South Africa and Zimbabwe. This area is well-known for its varied topography, which includes bushveld and savannah, as well as important natural and cultural landmarks like the esteemed Mapungubwe National Park. Historically, Musina has been successful in trade, farming, and mining which have served as the main pillars of the economy. The town is well-known for having an abundance of mineral resources, including copper, iron ore, and coal, which have made investments and created jobs that have greatly boosted the local economy. The Save Mapungubwe Coalition has been having concerns about “the possible dangerous precedent set by the lack of clarity of the offset created by this agreement. The offset agreement is an important tool for ensuring that (Coal of Africa) CoAL restores all of the ecosystems that have been depleted as a result of their mining activities” (Melissa, 2014). They emphasise the danger mining operations have on archaeological sites and the ecological balance of the Vhembe Region. This dissertation aims to unpack the historical dimensions of eco-centric architecture, particularly focusing on the nuanced relationship between indigenous African mining practices and the surrounding landscapes. It seeks to shed light on the intricate balance between culture, spirituality, heritage, and the extractive mining industry. By examining the temporality of mining and the transient nature of the miner’s experience by looking at lungs as the metaphor of the temporality of breathing. Through a critical analysis of guiding principles employed in eco-centric architecture, this dissertation aims to explore the potential significance of what a building means in a landscape where biodiversity, culture, spirituality, heritage, and mining coexist. This dissertation will address post-mining landscapes through land reparation and restitution, the idea of Land Reparation and Restitution in this dissertation aims to extend beyond environmental rewilding, restoration by studying the legal framework of mining in South Africa and integrating social justice, heritage, and ecological sustainability strategies. The historian Pulido states: “Not merely about returning land to those who were displaced but also about restoring the relationship between people and the land that sustains them” (Pulido, 2018). The land court symbolizes transformation, reconciliation and justice for the environment, biodiversity, and human life. In the context of Musina, this thesis will explore ways of reparation can be conceptualised and executed given the interconnectedness histories of mining, colonization, and indigenous land use in Musina. The land Court will not only solve mining issues in Musina, but it will be advocating for land mining disputes around South Africa. It is influenced by concerns raised by the Save Mapungubwe Coalition regarding the proposed Industrial Park by the Special Economic Zone (SEZ), South Africa’s landscapes are not only resourced but hold so much history, archaeological elements hence preserving these sacred landscape, historical mining site and indigenous knowledges are very important. Lynn Meskell explains that “Archives of cultural and spiritual heritage that reflect centuries of human-environment interaction” are important (Meskell, 2019). An area such as Musina, where we find a national archelogical site, the Mapungubwe Abstract Cultural landscape being approximately 7km from the Vele Colliery, has a coal mine is an indication a historical precedent that the coexistence of mining and scared site is not sustainable. “The Save Mapungubwe Coalition is made up of a diverse range of groups, with expertise in everything from conservation to water and even heritage resources.” (“Mapungubwe Watch - Wits University,” n.d.) Ultimately, it aims to address questions regarding the role of the landscape in addressing the challenges left behind by coal mining and, in turn, how we can embark on the journey of healing the scars inflicted on these environments through ecologically sound restoration efforts, all while honouring the cultural heritage inherent in the site. Through the legal lens, how can we reimagine a land court that advocates for sacred landscapes, community including the mine workers’ lives?
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Lekgotla; Reclamation; Transient Landscapes; Phytoremediation; Post-critical ecophenomenology; SDG-13: Climate action; SDG-15: Life on land